2022
DOI: 10.1186/s13041-022-00897-9
|View full text |Cite
|
Sign up to set email alerts
|

The increased in vivo firing of pyramidal cells but not interneurons in the anterior cingulate cortex after neuropathic pain

Abstract: Chronic pain damages the balance between excitation and inhibition in the sensory cortex. It has been confirmed that the activity of cortical glutamatergic pyramidal cells increases after chronic pain. However, whether the activity of inhibitory interneurons synchronized changed remains obscure, especially in in vivo conditions. In the present study, we checked the firing rate of pyramidal cells and interneurons in the anterior cingulate cortex, a main cortical area for the regulation of nociceptive informatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…For example, studies of brain EEG associated with PyrNs firing suggest that high levels of beta in the right hemisphere are associated with anxiety symptoms. In contrast, high levels of alpha in the left hemisphere indicate depressive features [136][137][138].…”
Section: Pyramidal Neuronsmentioning
confidence: 93%
“…For example, studies of brain EEG associated with PyrNs firing suggest that high levels of beta in the right hemisphere are associated with anxiety symptoms. In contrast, high levels of alpha in the left hemisphere indicate depressive features [136][137][138].…”
Section: Pyramidal Neuronsmentioning
confidence: 93%
“…Pain withdrawal mechanical threshold (PWMT) of the left hind paw was tested via a range of Von-Frey filaments (Stoelting Company, Wood Dale, USA) as previous studies reported [ 26 , 27 ]. Briefly, mice were placed in metal mesh grids (7 × 7 × 10 cm 3 ) for 30 min before MPWT tests, which were applied at the same time point on baseline (days 0), days 1–7 after CFA/saline treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We consider the evolution of life in terms of the sequence of transformation of molecular chirality into cell chirality and bilaterality of organisms [24,27,[192][193][194]. Our hypothesis highlights the formal consequences of three co-existent events: molecular chirality, PyNs' shape, and bilateral body-brain morphology [195].…”
Section: From Molecular To Cell Chiralitymentioning
confidence: 99%